Patient time costs attributable to healthcare use in diabetes: results from the population‐based KORA survey in Germany. Issue 10 (24th July 2013) - Icks, A.; Claessen, H.; Strassburger, K.; Waldeyer, R.; Chernyak, N.; Jülich, F.; Rathmann, W.; Thorand, B.; Meisinger, C.; Huth, C.; Rückert, I.‐M.; Schunk, M.; et al.
Abstract Aims Patient time costs have been described to be substantial; however, data are highly limited. We estimated patient time costs attributable to outpatient and inpatient care in study participants with diagnosed diabetes, previously undetected diabetes, impaired glucose regulation and normal glucose tolerance. Methods Using data of the population‐based KORA S4 study (55–74 years, random sample of n = 350), we identified participants' stage of glucose tolerance by oral glucose tolerance test. To estimate mean patient time costs per year (crude and standardized with respect to age and sex), we used data regarding time spent with ambulatory visits including travel and waiting time and with hospital stays (time valued at a 2011 net wage rate of €20.63/h). The observation period was 24 weeks and data were extrapolated to 1 year. Results Eighty‐nine to 97% of participants in the four groups (diagnosed diabetes, undetected diabetes, impaired glucose regulation and normal glucose tolerance.) had at least one physician contact and 4–14% at least one hospital admission during the observation period. Patient time [h/year (95% CI)] was 102.0 (33.7–254.8), 53.8 (15.0–236.7), 59.3 (25.1–146.8) and 28.6 (21.1–43.7), respectively. Age–sex standardized patient time costs per year (95% CI) were €2447.1 (804.5–6143.6), €880.4 (259.1–3606.7), €1151.6 (454.6–2957.6) and €589.2 (435.8–904.8). Conclusions Patient time costs were substantial—even higher than medication costs in the same study population. They are higher in participants with diagnosed diabetes, but also in those with undetected diabetes and impaired glucose regulation compared with those with normal glucose tolerance. Research is needed in larger populations to receive more precise and certain estimates that can be used in health economic evaluation.